(untitled) (Communications in Computational Physics, 2007)
In this paper we develop a deterministic numerical method for solving the Boltzmann transport equation for semiconductors based on a transport-collision time-splitting method. Transport phases are solved by means of accurate flux-balance methods while collision steps are computed in the original k-grid. Numerical experiments are shown allowing for a discussion of this method with respect to other present in the literature.